Value of Confocal Microscopy of the Cornea in Assessment of the Adaptation Period at Patients with Myopia when Using Orthokeratological Lenses - E. A. Ezhova; I. A. Melikhova; S. V. Balalin (Oftalʹmologiâ, 2018)
Purpose: tо study the histomorphological state of the cornea with the help of confocal microscopy in patients with myopia in the period of adaptation to orthokeratological contact lenses (OCL).Patients and methods. The study of the histomorphological status of the cornea was performed in the central optical, middle peripheral and perilimbal zones using confocal microscopy (ConfoScan-4) in 72 patients (144 eyes) with low myopia (38 people, 76 eyes) and middle myopia (34 persons, 68 eyes) after the appointment of OCL within 1 to 12 months.Results. The maximum significant increase in the degree of epithelial changes in the central optical zone of the cornea was recorded after 7 days of the application of OCL and an increase of nerve fibers activation, the number of activated keratocytes — after 1 month. There were noted the degree of changes in the epithelium, the number of activated keratocytes after 1 month and the degree of activation of nerve fibers after 3 months in the middle peripheral zone of the cornea. At a period of 12 months of the using of OCL in the central optical zone and middle peripheral zone of the cornea the index of the degree of changes in the epithelium, nerve fibers, and the number of activated keratocytes was stabilized. In the perilimbal zone of the cornea the histomorphological parameters did not differ from the initial data at the observation periods, except for innervation. The densities of keratocytes in various layers of the stroma, endothelial cells did not change statistically throughout the study.Conclusions. The results of the histomorphological indices made it possible to single out a “stressful” period of adaptation lasting 1 month, a transitional period of 1 to 3 months and a stable adaptation period, the formation of which was noted after 12 months of the application of OKL. Stable densities of keratocytes in various layers of the corneal stroma, endothelial cells during the entire period of observation indicated a fairly good tolerability of OCL.